2016
DOI: 10.1016/j.rchipe.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Fanconi y raquitismo hipofosfatémico asociado al uso de tenofovir en una niña infectada con VIH

Abstract: Síndrome de Fanconi y raquitismo hipofosfatémico asociado al uso de tenofovir en una niña infectada con VIH AbstractIntroduction: Tenofovir (TDF) is an inhibitor of reverse transcriptase nucleotide analogue, although it has good tolerability and high anti-retroviral activity, its effect on the kidney has been a concern. Objective: To describe a girl infected with HIV who presented Fanconi syndrome during antiretroviral therapy with TDF. Clinical case: We describe a HIV-1-infected girl, who after 18 months trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…For example, Tenofovir is the most frequently used component for HAART recommended by WHO. Concurrently, it has been reported that Tenofovir affects human kidney due to its renal toxicity and causing Fanconi’s syndrome, reduction in the glomerular filtration rate (eGFR) and acute kidney injury (AKI) 36 . Hence, less nephrotoxic drugs and simultaneously frequent monitoring of the kidney is preferable for HAART treatment in the Asian Scenario 7 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tenofovir is the most frequently used component for HAART recommended by WHO. Concurrently, it has been reported that Tenofovir affects human kidney due to its renal toxicity and causing Fanconi’s syndrome, reduction in the glomerular filtration rate (eGFR) and acute kidney injury (AKI) 36 . Hence, less nephrotoxic drugs and simultaneously frequent monitoring of the kidney is preferable for HAART treatment in the Asian Scenario 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Un síndrome de malabsorción era improbable por los niveles normales de 25 (OH) D 3 y la ausencia de síntomas gastrointestinales; no se solicitaron anticuerpos anti endomisio ni anti transglutaminasa. Se descartó síndrome de Fanconi por la ausencia de otras pérdidas tubulares (9). Entre otros, no se encontró glucosuria, hipercalciuria ni acidosis metabólica.…”
Section: Rev Med Hered 2019; 30:262-266 265unclassified